An Analysis on Language Function in Utterances Produced by Carl to Russel in Movie “Up” - Silviani, Adilah; Sahril, Sahril; Abdullah, Abdullah (PERFORMANCE: JOURNAL OF ENGLISH EDUCATION AND LITERATURE, 2025)
The language function is a meanings of communications besides that the function of language is used to convey intent or purpose when speaking by adjusting the context. This research uses a qualitative descriptive method, in looking for two main focuses in this research, namely looking for types of language functions and the meaning of the use of language functions themselves which are analyzed in Card Fredricksen's conversation in the film Up 2009. This research uses Halliday's theory in 1992 which states that there are 7 types of language functions, namely instrumental function, regulatory function, heuristic function, representational function, interactional function, personal function and imaginative function. Research found that there were 21 extracts in the 2009 film Up, only five types of language functions were found out of seven types of language functions according to Halliday (1992). Two types of language functions that have not been discovered by researchers are personal functions and representational functions. In the instrumental function, there were 4 extracts found by researchers, found in extracts 1-4. Next, the regulatory function, researchers found that there were 11 extracts, this type was the most important. The next type is interactional function, researchers only found 4 extracts. while the heuristic function and imaginative function, researchers only found one of each of these two types. The heuristic function is found in extract 20 while the imaginative function is found in extract 21.Keywords: language, language function, movie, Disney, character.